(W)hole new field: the new GEM Time Projection Chamber of ALICE. (June 2020) - Miśkowiec, Dariusz
Abstract: The ALICE Time Projection Chamber has just been upgraded by replacing the readout chambers, which cover the two ends of the cylinder, with new detectors based on the Gas Electron Multiplier (GEM) technology. We report here on the related activities at GSI Darmstadt: GEM framing and chamber production, as well as the quality assurance accompanying both procedures.